Predictors of Dengue Hemorrhagic Fever in the Pediatric Population: Logistic Regression Analysis of Hematological Profile and Demographics - Ari Nuswantoro; Agus Dimas Ratulangi (Universitas Tribhuwana Tunggadewi, 2026)
Dengue Hemorrhagic Fever (DHF) remains a significant public health threat in Indonesia, particularly among the pediatric population. Early diagnosis is crucial for appropriate clinical management, and hematological parameters are routinely available indicators that may aid in predicting dengue infection. However, the independent predictive value of individual hematological parameters for NS1-confirmed dengue in children remains not fully characterized. This study aimed to identify independent predictors of NS1-positive dengue hemorrhagic fever in the pediatric population through logistic regression analysis of hematological profiles and demographic characteristics. A cross-sectional analytical study was conducted using secondary data from medical records of pediatric patients admitted to the pediatric ward of RSUD dr. Soedarso Pontianak between January and December 2023. A total of 203 patients who underwent NS1 antigen testing and complete hematological examinations were included. Data were analyzed using bivariate tests (independent t-test or Mann-Whitney U test) followed by binary logistic regression to identify independent predictors of NS1 positivity. Model performance was evaluated using Receiver Operating Characteristic (ROC) curve analysis. Bivariate analysis revealed that thrombocyte count was significantly lower in NS1-positive patients compared to NS1-negative patients. In multivariate logistic regression analysis, thrombocyte count emerged as a significant negative predictor of NS1 positivity, while erythrocyte count demonstrated a significant positive association. Hemoglobin, hematocrit, leukocyte count, age, and sex did not retain statistical significance in the final model. The combination of thrombocyte and erythrocyte counts yielded acceptable discriminative ability with an area under the ROC curve of 0.68. Thrombocyte count and erythrocyte count are independent predictors of NS1-positive dengue infection in pediatric patients. Low thrombocyte counts and elevated erythrocyte counts increase the likelihood of acute dengue infection and should be considered in diagnostic assessment, particularly in resource-limited settings where immediate NS1 testing may not be available.